Role of Tc-99m RBC Scintigraphy in Specific Diagnosis of Giant Hepatic Hemangioma: a Case Report (Bangladesh Journal of Nuclear Medicine, 2016)
Hemangioma is one of the most common benign liver tumors. They are mostly asymptomatic. Differentiating hemangiomas from malignant tumoral lesions and metastases by a non invasive method is very important. We report a asymptomatic case with incidental finding of a large massive hemangioma occupying almost whole of the right lobe of liver and emphasized its detection by Tc-99m red blood cell (RBC) three phase imaging and localization of the tumor.Bangladesh J. Nuclear Med. 17(2): 153-155, July 2014